2008
DOI: 10.1037/1938-8926.1.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Does diversity at undergraduate institutions influence student outcomes?

Abstract: Using two separate samples, this study establishes and replicates a model of the influence of two types of educational diversity on student outcomes. Study 1, using survey data regarding undergraduate experiences from a volunteer sample of 1,963 incoming law students, confirms measurement models for diversity and outcome constructs and tests models predicting student outcomes from Classroom Diversity and Contact Diversity. Study 2 utilizes data from a nationally representative sample of 6,100 incoming law stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 17 publications
2
50
0
Order By: Relevance
“…Analyses of the MSS data found a relationship between diversity experiences and greater perspective taking among White students (Gurin et al, 2004). Similarly, students with more diversity-course enrollment showed more empathy regarding prejudice (Spanierman, Todd, & Anderson, 2009) and greater enthusiasm for learning about new perspectives (Gottfredson et al, 2008). Taken together with the mediation studies involving willingness to consider other perspectives and related variables, these data suggest a promising role for perspective taking and empathy in mediating the diversity experience-intergroup attitude relationship.…”
Section: Theory and Empirical Results Suggesting Additional Mediatingmentioning
confidence: 80%
See 1 more Smart Citation
“…Analyses of the MSS data found a relationship between diversity experiences and greater perspective taking among White students (Gurin et al, 2004). Similarly, students with more diversity-course enrollment showed more empathy regarding prejudice (Spanierman, Todd, & Anderson, 2009) and greater enthusiasm for learning about new perspectives (Gottfredson et al, 2008). Taken together with the mediation studies involving willingness to consider other perspectives and related variables, these data suggest a promising role for perspective taking and empathy in mediating the diversity experience-intergroup attitude relationship.…”
Section: Theory and Empirical Results Suggesting Additional Mediatingmentioning
confidence: 80%
“…In studies employing majority White samples, participation in diversity courses did not impact quantity of interactions with diverse peers but it did relate to more positive contact experiences with diverse peers (Laird, 2005). Also, curricular experiences such as attending racial/cultural awareness programs and discussion of racial issues related to greater frequency of cross-ethnic contact (Gottfredson et al, 2008). In each of the studies cited, the observed effects appear relatively small (e.g., correlation of <.40).…”
Section: Evidence For the Distinctiveness Of Diversity Experiences Anmentioning
confidence: 99%
“…These findings demonstrate the importance of intentionally designed intercultural interactions. In addition, several studies have concluded that it is important to provide sustained and coordinated efforts across and throughout the undergraduate experience in order to maximize the benefits of diversity on student development and learning (Gottfredson et al 2008;Gurin et al 2002) and to achieve the level of intercultural competency required to participate effectively and thoughtfully in diverse settings in our communities and workplaces (AAC&U 2010). For institutions and practitioners seeking to improve diversity-related outcomes, these findings draw attention to classes and the need to investigate how they can be intentionally designed so as to "activate" (Marin 2000) the diversity resources present in order to encourage students to develop, test, apply, and reflect upon the ability to use and build upon new knowledge.…”
Section: Interactions With Diverse Peers and Curriculamentioning
confidence: 99%
“…Diversity is frequently conceptualized in terms of racial and ethnic identity and defined in the higher education context in three ways: 1) structural diversity, i.e., the demographic diversity of a campus; 2) interactional diversity, i.e., deliberate and facilitated interactions with structural diversity; and 3) curricular diversity, i.e. diverse ideas and peers in classroom or cocurricular contexts (Bowman 2010a;Gottfredson et al 2008;Gurin et al 2002).…”
Section: Key Concepts: Engaging Diversity and Inclusive Excellencementioning
confidence: 99%
“…Diversity can also have important social and educational outcomes, such as "greater learning, increased interpersonal competencies, greater self-confidence among students, fewer irrational prejudices, greater gains in critical thinking, and greater involvement in civic and community service" (Worthington et al 2008:8). Gottfredson et al (2008) report that both diversity in the classroom and more informal "contact diversity" in other campus activities were positively related to such factors as cognitive openness, positive attitudes towards equal opportunities and academic outcomes.…”
Section: The Determinants Of Quality Of Life For University Students:mentioning
confidence: 99%